Greater accountability in nursing handover - Yusrita Zolkefli (Belitung Raya Foundation, Indonesia, 2022)
Nursing handover exemplifies both the nurse’s professional ethics and the profession’s integrity. The article by Yetti et al. acknowledges the critical role of structure and process in handover implementation. At the same time, they emphasised the fundamental necessity to establish and update handover guidelines. I assert that effective patient handover practices do not simply happen; instead, nurses require pertinent educational support. It is also pivotal to develop greater professional accountability throughout the handover process. The responsibility for ensuring consistent handover quality should be shared between nurse managers and those who do the actual handover practices.